Digital Gender Gap for Housewives - Lestari, Anna Puji; Sunarto, Sunarto (Jurnal The Messenger, 2018)
The development of communication technology through the internet brings a digital gap for women, especially for housewives who tend to be associated with domestic work. This study examines the use of internet and web newspaper (suaramerdeka.com) access by housewives. This study breaks the patriarchal ideology and the digital gap in family communication in the terms of access to information via internet. The theory used in this study is Gender Structure and Liberal Feminist Theories. This study is a descriptive qualitative research with critical phenomenology design. The results of study suggest that housewives are still excluded from access to information via internet due to unequal power in the use of communication technology in families. This happens because of the pattern of family communication that embraces patriarchy culture believing that housewives only need to take care of domestic issues and do not require internet access.